1997
DOI: 10.1523/jneurosci.17-02-00786.1997
|View full text |Cite
|
Sign up to set email alerts
|

The Neuronal Basis of the Behavioral Choice between Swimming and Shortening in the Leech: Control Is Not Selectively Exercised at Higher Circuit Levels

Abstract: Swimming and the whole-body shortening reflex are two incompatible behaviors performed by the medicinal leech Hirudo medicinalis. We set out to examine the neuronal basis of the choice between these behaviors, taking advantage of the fact that the neuronal circuit underlying swimming is relatively well understood. The leech swim circuit is organized hierarchically and contains three interneuronal levels, including two upper levels of "command-like" neurons. We tested the responses of the swim circuit neurons t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 39 publications
2
51
0
Order By: Relevance
“…Neurons Tr1, SE1, and R3b1 initiate swimming (Brodfuehrer and Friesen, 1986a,b,c;Thorogood and Brodfuehrer 1995;Shaw and Kristan, 1997;Esch et al, 2002), whereas neurons SIN1 and Tr2 terminate swimming O'Gara and Friesen, 1995). The firing of neuron R3b1 (Esch et al, 2002) elicits both swimming and crawling or a hybrid behavior (similar to that shown in Fig.…”
Section: Flow Of Leech Behavioral Decisions As a First-order Markov Pmentioning
confidence: 58%
See 2 more Smart Citations
“…Neurons Tr1, SE1, and R3b1 initiate swimming (Brodfuehrer and Friesen, 1986a,b,c;Thorogood and Brodfuehrer 1995;Shaw and Kristan, 1997;Esch et al, 2002), whereas neurons SIN1 and Tr2 terminate swimming O'Gara and Friesen, 1995). The firing of neuron R3b1 (Esch et al, 2002) elicits both swimming and crawling or a hybrid behavior (similar to that shown in Fig.…”
Section: Flow Of Leech Behavioral Decisions As a First-order Markov Pmentioning
confidence: 58%
“…An automatic system based on imaging with a CCD camera tracked three colored beads attached to the back of the leech and recorded its motion for up to 12 h. Statistical analysis based on the kinematic and spectral content of the leech motion (Mazzoni et al, 2005) allowed unambiguous classification of Ͼ90% of the leech motion into characteristic behavioral categories. We found that the mechanism by which the leech decides its behavior is adequately described by a Markov process, the transition rates of which are probably controlled by the firing of command-like neurons found in the leech head ganglion O'Gara and Friesen, 1995;Shaw and Kristan, 1997;Esch et al, 2002).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Such an outcome could be considered in the context of behavioral choice (e.g., Shaw and Kristan, 1997;Briggman et al, 2005;Körding and Wolpert, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This coding scheme has received the most attention in studies involving a directed response (Georgopoulos et al, 1986;Sparks, 1988;Georgopoulos, 1995;Lewis and Kristan, 1998a,b;Lewis, 1999), but it can be extended to include categorically distinct behaviors . A recent hypothesis proposes that different motor behaviors result from different combinations of activity patterns in overlapping but distinct combinations of multifunctional neuronal inputs to motor circuits Shaw and Kristan, 1997). With respect to sensory-evoked activation of the descending reticulospinal neuron system that activates the spinal locomotor network or the VCN-evoked activation of projection neurons that activate the gastric mill circuit, the resulting network and behavioral output also result from activity that is represented across a population of descending inputs.…”
mentioning
confidence: 99%